Endovascular repair of infrarenal aortic aneurysms in octogenarians and nonagenarians - Geisbüsch, Philipp; Katzen, Barry T.; Tsoukas, Athanassios I.; Arango, Dillon; Peña, Constantino S.; Benenati, James F. (Journal of vascular surgery, 2011)
Objective - The purpose of this report was to present short and midterm results of endovascular aortic aneurysm repair (EVAR) of infrarenal aortic aneurysms in octogenarians and nonagenarians. - Methods - Between March 1994 and March 2011, elective EVAR was performed in 967 patients in our institution. This includes 279 patients older than 80 years at the time of the procedure (octogenarians: n = 252, nonagenarians: n = 27). Mean follow-up was 48.4 ± 34.5 months. A retrospective analysis was performed. Survival was calculated using Kaplan-Meier analysis and a survival comparison to patients who underwent EVAR <80 years old (n = 688) was performed. Cox hazard regression analysis was used to assess parameters that influence survival. - Results - Technical success was 96% in octogenarians and 85% in nonagenarians. Technical failure in 15 of 279 patients includes primary type I endoleak (n = 6), procedure abortion due to inability to pass the iliac vessels (n = 6), and emergency conversion (n = 3). Thirty-day mortality was significantly higher for patients >80 years old (2.8% vs 1.0%; P = .044). Morbidity rates were 11.5% for octogenarians and 7.4% for nonagenarians with predominately cardiopulmonary complications. High-risk patients >80 years old showed a comparable perioperative mortality rate to low-/medium-risk patients >80 years old (2.9% vs 2.5%;P = .717), but a significantly higher complication rate (22.5% vs 9.2%; P = .0275) and reduced midterm survival with 1-, 3-, and 5-year survival rates of 79% ± SE 7%, 55% ± SE 8%, and 38% ± SE 9% (log-rank test P = .03). In high-risk patients age >80 years old, their age did not influence 30-day mortality (2.5% vs 2.7%; P = .978) and midterm survival. Survival in octogenarians at 1, 3, and 5 years was 87.9 ± SE 2.1%, 70.9 ± SE 3.0%, and 55.6% ± SE 3.5%, respectively. Survival in nonagenarians at 1 and 3 years was 96.3% ± SE 4% and 60.6% ± SE 10.4%. Higher cardiac (hazard ratio [HR], 1.22; P = .038) and renal risk scores (HR, 1.59; P = .0016), chronic obstructive pulmonary disease (HR, 1.56; P = .032), and anemia (HR, 2.1; P < .001) influenced midterm survival. - Conclusion - EVAR in octogenarians and nonagenarians is associated with a significantly higher but still low perioperative mortality compared to younger patients. Midterm survival in octogenarians and nonagenarians, although significantly lower than in younger patients, is still acceptable, indicating that age >80 years should not be an exclusion criteria for EVAR. Even high-risk patients >80 years can be treated safely with a low perioperative mortality and comparable midterm outcome to younger high-risk patients.